EFFORTS TO INCREASE THE RESILIENCE OF MUSLIM FAMILIES IN CINERE DISTRICT, DEPOK CITY - Mulauddin, Aforisma; Muslim, Muslim; Fachrudin, Fachri (STAI Al-Hidayah Bogor, 2024)
This study aims to enhance the resilience of Muslim families in Cinere Subdistrict, Depok City, through a series of community service activities. These activities were conducted by lecturers and students of STAI Al-Hidayah Bogor in collaboration with Majelis Ilmu Annisa, involving various programs such as Islamic studies, lifestyle consultations, and the distribution of basic necessities. The primary target group is women involved in Majelis Ta'lim and economically disadvantaged communities vulnerable to attempts at proselytization. The research methods include observation, study, consultation, and evaluation. The results show an increase in Islamic awareness and knowledge, strengthening of faith, and solidarity among Muslims. These activities also provide benefits for the academic community in understanding and directly addressing community issues.